Turner's Syndrome: Approach to Diagnosis and Treatment - Sah, Sadhana; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Jha, Umesh; Bharati, Sonu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Turner's syndrome is the most common karyotypic abnormality causing gonadal failure and primary amenorrhea. It is characterized by short stature and absence of secondary sexual characteristics. It is diagnosed by increased plasma FSH and LH level with low level of estrogen i.e. hypergonadotrophic hypogonadism. Ultrasound abdomen reveals streak ovaries and atrophic uterus. Karyotype confirms the diagnosis of Turner's syndrome (45XO).We present here a 15 years girl who presented with primary amenorrhea with short stature with breast development corresponds to Tanner stage I. Her FSH was raised. Ultrasound abdomen showed uterine agenesis and streak ovaries. Karyotype showed 45XO which confirmed the diagnosis of Turner's syndrome. She is now on estrogen therapy and her height has increased and breast development corresponds to Tanner stage II.Keywords: hypergonadotrophic hypogonadism, primary amenorrhea, Turner's syndrome